The protective role of Kombucha extract on the normal intestinal microflora, high-cholesterol diet caused hypercholesterolemia, and histological structures changes in New Zealand white rabbits - Alaei, Zeytoon (Avicenna J Phytomed, 2020)
OBJECTIVE: The aim of the current study was to investigate the effect of Kombucha extract (tea) on the normal intestinal microflora and histological structures in rabbits. MATERIALS AND METHODS: This study was a descriptive-analytical investigation. Thirty-two male New Zealand rabbits were randomly divided into 4 groups as follows: Normal diet (I), high-cholesterol diet (II), normal diet plus Kombucha extract (II), and high-cholesterol diet plus Kombucha extract (IV). Microbial cultures were taken from feces of rabbits before and after the applied treatments. The rabbits' blood was collected from the heart to determine the level of cholesterol, glucose and iron in the blood. Aorta and coronary heart microtome cut samples were prepared for detection of histological changes. RESULTS: Rabbit stool cultures before treatment with Kombucha extract included Enterobacter aerogenes, Providencia rettgeri, Proteus mirabilis, Pseudomonas aeruginosa and Klebsiella oxytoca. However, Escherichia coli, Enterobacter aerogenes, Pseudomonas aeruginosa, klebsiella pneumoniae and Hafnia alvei were found in stool cultures after treatment with Kombucha extract. Group IV had significantly lower blood cholesterol levels. Animals that received Kombucha extract only had lower fasting blood sugar (FBS) levels. Healthy rabbits that received Kombucha extract only and group (IV) showed a significant increase in iron (Fe) levels and a significant decrease in total iron binding capacity (TIBC) levels. In both groups III and IV, the right and left coronary arteries were completely normal and no lesions were observed in the intima. CONCLUSION: The results of this study showed minor changes in the intestinal microflora of rabbits after treatment with Kombucha extract and positive effects of this tea on some risk factors (hypercholesterolemia, arteriosclerosis, and FBS).